1996
DOI: 10.1111/j.1365-3040.1996.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

The water relations of the root–soil interface

Abstract: The difference in hydrostatic pressure between the xylem of the leaf and the soil depends, for a given transpiration rate, on the series of hydraulic resistances encountered along this pathway. Many studies have shown that the sum of the resistances in the plant and the soil is too small to account for the fall in water pressure between the leaf xylem and the soil, especially when plants are growing in sandy soils, which are prone to dry rapidly. A resistance at the root–soil interface, caused possibly by poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 30 publications
1
57
0
2
Order By: Relevance
“…However the measurements of Steudle (1993) have indicated that in most cases cell membrane reflection coefficients are near unity. We feel that the generally low value of W, compared with the nutrient solution, might result from the presence of solutes in the apoplasm (cell-wall solutes), perhaps as solutes accumulated at the root surface during mineral uptake, or as solutes leak from the cell membranes (Cosgrove & Cleland, 1983;Stirzaker & Passioura, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However the measurements of Steudle (1993) have indicated that in most cases cell membrane reflection coefficients are near unity. We feel that the generally low value of W, compared with the nutrient solution, might result from the presence of solutes in the apoplasm (cell-wall solutes), perhaps as solutes accumulated at the root surface during mineral uptake, or as solutes leak from the cell membranes (Cosgrove & Cleland, 1983;Stirzaker & Passioura, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be further increased due to a decrease in soil-root hydraulic conductance related to root shrinkage, which severely hampers water flow to roots (Carminati et al, 2009 and Willatt, 1983). Recent observations point to a rhizospheric effect onto the water relations of this soil-root interface, involving mucilages, root exudates and possibly solute accumulation (Carminati and Vetterlein, 2013;McCully et al, 2009;Read et al, 2003;Stirzaker and Passioura 1996), which would modulate soil-root contact and water uptake with variations in dry or moist soil (White and Kirkegaard, 2010).…”
Section: Roots and Root-soil Interactionsmentioning
confidence: 99%
“…This effect can be further increased due to a decrease in soil-root hydraulic conductance related to root shrinkage, which severely hampers water flow to roots (Carminati et al, 2009 and Willatt, 1983). Recent observations point to a rhizospheric effect onto the water relations of this soil-root interface, involving mucilages, root exudates and possibly solute accumulation (Carminati and Vetterlein, 2013;McCully et al, 2009;Read et al, 2003;Stirzaker and Passioura 1996), which would modulate soil-root contact and water uptake with variations in dry or moist soil (White and Kirkegaard, 2010).At longer time scales, not only plasticity in water relations but also in root growth will occur during water deficit, with a decrease in root length (reduced growth, increased mortality) in drier parts and an increase in wetter parts (Huang and Eissenstat, 2000;Sekhon et al, 2010). If an increase in root growth can be observed at the onset of water stress, the continuing drought will reduce the overall root growth, resulting from uncoupling between carbon production in leaves and use in root sinks (root apex) (Muller et al, 2011).…”
mentioning
confidence: 99%
“…The significance of both Ψ pd and Ψ min as indicators of plant water status has been questioned. As an example, Ψ pd has been reported not to coincide with soil water potential [3,8,43] during dry periods due to an air gap between roots and soil [53]. In other cases (e.g.…”
Section: Introductionmentioning
confidence: 99%